2022
DOI: 10.3389/fpls.2022.893055
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis Identifies Differences Between Wild and Domesticated Chili Pepper Fruits During Development (Capsicum annuum L.)

Abstract: Capsicum spp. members are a rich source of specialized compounds due to their secondary metabolism. Some metabolic pathways have suffered modifications during the domestication process and improvement of agricultural traits. Here, we compared non-targeted LC–MS profiles from several areas: wild accessions (C. annuum L. var. glabriusculum), domesticated cultivars (C. annuum L.), and the F1 progeny of a domesticated, and a wild accession cross (in both directions) throughout seven stages of fruit development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
1
5
0
1
Order By: Relevance
“…Amino acid metabolism enrichment is crucial to affect metabolic process post pathogen interaction 68 . Overall, the enrichment analysis indicated high abundance of metabolite hits in different pathways and their dominance revealed modulation of plant responses towards defense, resistance and/or survival 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid metabolism enrichment is crucial to affect metabolic process post pathogen interaction 68 . Overall, the enrichment analysis indicated high abundance of metabolite hits in different pathways and their dominance revealed modulation of plant responses towards defense, resistance and/or survival 69 .…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids have a range of biological activities in plants, such as antioxidant activities, antimicrobial activities, signaling, and defense against environmental stressors [ 42 ]. It has been reported that the flavonoids biosynthesis pathway was one of the most affected during the domestication and selection of chili pepper [ 43 ]. We suspected that the Lucha varieties strengthened this route to cope with the cold weather or other adverse environments in Shandong.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration and application of ABA were as described in previous studies with slight modifications (Casey Barickman et al ., 2014; Cervantes-Hernández et al ., 2022; Liu et al ., 2017). Briefly, mature green (30 DPA) pepper fruit of the inbred line ‘59’ was treated with 50 μM ABA (Sigma-Aldrich, USA).…”
Section: Discussionmentioning
confidence: 99%